The Nigerian Male: Changing Gender Roles and Relationships - Oladimeji, B. Y.; Odebiyi, A. I. (2014)
Gender-role specialisation is in the interest of system maintenance. Parents tend to socialize their children to assume the gender-roles so that the smooth running of the family is maintained. However, with urbanization and socio-economic changes, women are now in jobs and professions traditionally viewed as "the preserves" of men. The opportunity for more women taking leadership role in the community at large has widened. The present study was designed to thrown some light on the attitude of Nigerians towards the changing gender roles. Are there changes in perception that could possibly be a source of conflict, which could disrupt the family system. To determine this, a masculine values inventory was administered on men in 250 households in Ile-Ife, using a systematic random sampling technique. Attitude to marriage and inter-relationship between husbands and wives, work, family and economic responsibilities were explored. The findings revealed the ambivalent attitude of men towards the changing gender roles and relationships, highlighting the need for carefully designed public awareness and education programmes, directed at the male population as decisive partners in progress.